Genomic and epigenomic landscape of ADPKD: towards precision diagnostics and tailored treatments - Salybekov, Amankeldi A.; Kinzhebay, Aiman; Hidaka, Sumi; Kobayashi, Shuzo (Frontiers in Epigenetics and Epigenomics, 2026)
Autosomal dominant polycystic kidney disease (ADPKD) represents one of the most prevalent hereditary renal disorders, affecting an estimated 12.5 million individuals globally and characterized by progressive cyst formation in both kidneys. While mutations in PKD1 and PKD2 genes account for most cases, recent research has identified rare causative genes as contributing factors in genetically unresolved cases. The review examines the molecular mechanisms of cystogenesis, highlighting how genetic predisposition interacts with epigenetic modifications, including DNA methylation patterns, histone alterations, and non-coding RNAs (miRNAs and piRNAs). Advanced diagnostic approaches, from conventional imaging to AI-assisted cyst segmentation and long-read sequencing technologies, are evaluated for their clinical utility. Long-read sequencing platforms increase diagnostic yield by up to 25% in previously unsolved cases, while AI-enhanced imaging provides superior accuracy in disease progression monitoring. Finally, the paper explores emerging precision medicine strategies, including targeted therapies directed at specific molecular pathways, risk stratification algorithms, and personalized treatment approaches based on individual genetic and epigenetic profiles. This integration of genomic and epigenomic insights provides a foundation for improved prognostic models, early biomarkers, and tailored therapeutic interventions for ADPKD patients.